Social Entrepreneurship: Opportunitites Ahead - Tripathi, Lallan; Agarwal, B. K (Journal of Commerce and Trade, 2010)
The Indian society, especially rural is widely spread and is constituted by rich, poor and below poverty level (BPL) person. There is significance presence of BPL person in the society in spite of continuous effort made by Central Government, State Government, Mega sector enterprises and various Non Government Organizations (NGOs), therefore efforts to bring these categories in to mainstream of society byway of providing gainful employment/germinating the seeds of entrepreneurial culture is the demand of the day to develop prosperous and cheerful society. The philanthropic approach is narrow concept of elevating an individual and is not a long term solution of poverty eradication. The development of entrepreneurial culture among these class will bring multifold impact on improvement of the social dynamics, as it provide an opportunity to be self employed improving thereby their economic/ social status.The present paper is an endeavor to enlighten about the approaches and opportunities for the social entrepreneurship.